Perbandingan Pengaruh Core Exercise dan Senam Nifas terhadap Penurunan Lingkar Perut pada Perempuan Postnatal Spontan di RS Efarina Berastagi - Muliati, Muliati; Napitu, Marolop Parlindungan; Purba, Yeni Trisna; Saragih, Indra Riski (Jurnal Riset Hesti Medan, 2024)
Objective: To find out the comparison of the effect of giving core exercise and postpartum exercise to the decrease in abdominal circumference in spontaneous women. Method: The research method used is quasi-experimental with a pre-test and post-test design. The sample used was 30 people and divided into 2 groups who were given core exercise and postpartum gymnastics, each group amounted to 15 people. The measuring instrument used to measure the circumference of the respondent's abdomen is a measuring tape or midline. Results: The results of the paired t-test effect on the core exercise and postpartum exercise group obtained the same values, namely 0.000 (p<0.05). The results of the independent sample t-test obtained the results of 1.000 (p>0.05). Conclusion: There is no comparison of the effect of giving core exercise and postpartum exercise on the decrease in abdominal circumference in spontaneous postnatal women.